High level aminoglycoside resistance and distribution of the resistance genes in Enterococcus faecalis and Enterococcus faecium from teaching hospital in Malaysia - Moussa, A. A.; Md Nordin, A. F.; Hamat, R. A.; Jasni, A. S. (Dove Medical Press, 2019)
Background: Enterococcus faecium and Enterococcus faecalis are among the predominant species causing hospital-acquired infections. Currently, enterococcal infections are treated using combination therapy of an aminoglycoside with cell-wall active agents, which led to high level aminoglycoside resistance (HLAR) and vancomycin resistance (VRE) among enterococci. The aim of this study was to determine the prevalence of HLAR and the distribution of the resistance genes among clinical E. faecalis and E. faecium isolates in Malaysia. Materials and methods: Seventy-five enterococci isolates recovered from different clinical sources were re-identified by subculturing on selective medium, Gram staining, biochemical profiling (API 20 Strep), and 16s rRNA sequencing. Antimicrobial susceptibility testing (AST) was performed using Kirby-Bauer disc diffusion, E-test, and broth microdilution methods. PCR amplification was used to detect the presence of aminoglycoside modifying enzyme (AME) genes [aac(6’)-Ie-aph(2”)-Ia, aph(2”)-Ib, aph(2”)-Ic, aph(2”)-Id, aph(3’)-IIIa]. Descriptive data analysis was used to analyze the antibiotic susceptibility profiles and the distribution of HLAR genes. Results: The majority of the isolates recovered from the clinical samples are E. faecalis (66.7%), with the highest recovery from the pus. The prevalence of HLGR (51%) is higher when compared to HLSR (45–49%). Analysis of the resistance genes showed that bifunctional genes aac(6’)-Ie-aph(2”)-Ia and aph(3’)-IIIa contributed to the HLAR E. faecalis and E. faecium. The other AME genes [aph(2”)-Ib, aph(2”)-Ic, aph(2”)-Id] were not detected in this study. Conclusion: This study provides the first prevalence data on HLAR and the distribution of the AME genes among E. faecalis and E. faecium isolates from Malaysia. These highlight the need for continued antibiotic surveillance to minimize its emergence and further dissemination.